FGF10 Protects Against Renal Ischemia/Reperfusion Injury by Regulating Autophagy and Inflammatory Signaling - Tan, Xiaohua; Zhu, Hongmei; Tao, Qianyu; Guo, Lisha; Jiang, Tianfang; Xu, Le; Yang, Ruo; Wei, Xiayu; Wu, Jin; Li, Xiaokun; Zhang, Jin-San (Frontiers in Genetics, 2018)
Ischemia-reperfusion (I/R) is a common cause of acute kidney injury (AKI), which is associated with high mortality and poor outcomes. Autophagy plays important roles in the homeostasis of renal tubular cells (RTCs) and is implicated in the pathogenesis of AKI, although its role in the process is complex and controversial. FGF10, a member of the fibroblast growth factor (FGF) family, was reported to exert protective effects against cerebral ischemia injury and myocardial damage. Whether FGF10 has similar beneficial effect, and if so whether autophagy is associated with the potential protective activity against AKI have not been investigated. Herein, we found that FGF10 treatment improved renal function and histological integrity in a rat model of renal I/R injury. We observed that FGF10 efficiently reduced I/R-induced elevation in blood urea nitrogen, serum creatinine as well as apoptosis induction of RTCs Interestingly, autophagy activation following I/R was suppressed by FGF10 treatment based on the immunohistochemistry staining and immunoblot analyses of LC3, Beclin-1 and SQSTM1/p62. On the other hand, combined treatment of FGF10 with Rapamycin partially reversed the renoprotective effect of FGF10 suggesting the involvement of mTOR pathway in the process. Interestingly, FGF10 also inhibited the release of HMGB1 from the nucleus to the extracellular domain and regulated the expression of inflammatory cytokines such as TNF-α, IL-1β and IL-6. Together, these results indicate that FGF10 could alleviate kidney I/R injury by suppressing excessive autophagy and inhibiting inflammatory response and may therefore have the potential to be used as the prevention and perhaps treatment of I/R-associated AKI.